Cardioband system as a treatment for functional mitral regurgitation. (3rd June 2018) - Ferrero Guadagnoli, Adolfo; De Carlo, Carlotta; Maisano, Francesco; Ho, Edwin; Saccocci, Matteo; Cuevas, Oscar; Luciani, Marco; Kuwata, Shingo; Nietlispach, Fabian; Taramasso, Maurizio
ABSTRACT: Introduction : Are the current data on the Cardioband in the clinical area enough to consider it a tool for mitral regurgitation treatment? Severe secondary mitral valve insufficiency frequently affects high-risk surgical patients. The Cardioband system is a novel percutaneous surgical-like device for direct annuloplasty. It is implanted into the beating heart by transvenous femoral access, with minimal impact on hemodynamic and cardiac function during implantation. So far, it has demonstrated safety and feasibility in high-risk patients with functional mitral regurgitation; it has imparted significant annular reduction and regurgitation improvements. In well-selected patients, it could be an option for mitral valve repair. Areas covered : This is a bibliographic review based on scientific publications and medical congress reports. It includes the most current information related to Cardioband in mitral regurgitation. Expert commentary : This novel, less-invasive and effective tool is an option for the open repair or replacement of the mitral valve in high-risk surgical patients. Although the current results of Cardioband are promising, more data and longer follow-up times are necessary to confirm its safety and efficacy and to evaluate the durability of the results.